1980
DOI: 10.1097/00000658-198001000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder Carcinoma First Diagnosed at Microscopic Examination of Gallbladders Removed for Presumed Benign Disease

Abstract: The patients who survive gallbladder carcinomas more than five years are usually those in whom the carcinoma was first diagnosed at microscopic examination of gallbladders removed for presumed benign disease. A group of 32 such patients (from a series of 120 cases) was studied. The prognosis was very bad (longest survival 2.5 years) in 21 of the patients where the cancer involved all the layers of the gallbladder wall. The prognosis was far better in the 11 patients in which the cancer was confined to the muco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(30 citation statements)
references
References 11 publications
1
28
0
1
Order By: Relevance
“…Most long-term survivors have undergone cholecystectomy for cholelithiasis, with gallbladder carcinoma detected incidentally in the surgi cal specimen by the pathologist [1], Many authors, how ever, believe that treatment of carcinoma of the gallblad der should include cholecystectomy, resection of adjacent hepatic substance, and meticulous dissection of known areas of lymphatic drainage. This procedure has been termed extended (or radical) cholecystectomy [2][3][4][5], Based on an analysis of data from 15 and 10 patients treated by extended cholecystectomy, Glenn et al [6] and Evander et al [7] concluded that survival was not en hanced significantly by this procedure. However, other authors [1, 8.…”
mentioning
confidence: 99%
“…Most long-term survivors have undergone cholecystectomy for cholelithiasis, with gallbladder carcinoma detected incidentally in the surgi cal specimen by the pathologist [1], Many authors, how ever, believe that treatment of carcinoma of the gallblad der should include cholecystectomy, resection of adjacent hepatic substance, and meticulous dissection of known areas of lymphatic drainage. This procedure has been termed extended (or radical) cholecystectomy [2][3][4][5], Based on an analysis of data from 15 and 10 patients treated by extended cholecystectomy, Glenn et al [6] and Evander et al [7] concluded that survival was not en hanced significantly by this procedure. However, other authors [1, 8.…”
mentioning
confidence: 99%
“…Until the use of abdominal imaging techniques, such lesions were often an unsuspected finding, and the diagnosis was rarely established. 7,22,25 Based on a few recent studies using imaging modalities, it seems that lesions in the gallbladder can now be diagnosed at an early, curable stage. 9,10,23,25 Prognostically this could be quite critical as staging of the tumor is a factor in outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Although the preoperative diagnosis of a gallbladder carcinoma has been improved greatly by various imaging techniques, it is not rarely diagnosed intraoperatively or postoperatively [1, 2, 3]. Under these circumstances, especially in patients with advanced gallbladder carcinomas, reoperation is occasionally needed.…”
Section: Introductionmentioning
confidence: 99%